Designing a Scoring System for Differential Diagnosis From Reactive Thrombocytosis and Essential Thrombocytosis - Shen, Chih-Lung; Hsieh, Tsung-Cheng; Wang, Tso-Fu; Huang, Wei-Han; Chu, Sung-Chao; Wu, Yi-Feng (Frontiers in Medicine, 2021)
Background: Thrombocytosis is a common finding in hospitalized patients and is of two main types, essential thrombocytosis (ET) and reactive thrombocytosis (RT). It is important to distinguish the two due to increased risk of developing marrow fibrosis, acute leukemia, and thrombosis in the former. Molecular studies are the main tools to differentiate the two but are not available in all hospitals. We aimed to design a highly sensitive scoring system using routine lab data to classify thrombocytosis as essential or reactive. Methods: A total of 145 patients were enrolled in this study. Potential predictors included patient demographics and clinical laboratory parameters. Receiver operating characteristic curve analysis was used to decide the optimal cutoff level. Multivariate logistic regression with forward model selection method was performed to decide the predictors. Results: The risk scores by multivariate analysis were as follows: 1 point for WBC > 13500/μL; 2.5 points for Hb > 10.9 g/dL; 3 points for platelet count > 659000/μL; and 2 points for MPV > 9.3 fL. The cut off value was set as 4.5 points, and sensitivity of 91.1% and specificity of 75.8% were noted. Conclusion: In this study, we investigated lab data and developed a high-sensitivity convenient-to-use scoring system to differentiate ET from RT. The scoring system was assigned to the resulting model to make it more economical, simple, and convenient for clinical practice.